Electrical energy generation by squeezing a graphene-based aerogel in an electrolyte. Issue 17 (26th April 2021) - Zhou, Xiaoshuang; Chen, Xin; Zhu, Hao; Dong, Xu; Li, Lvzhou; Cheng, Guanggui; Zhang, Zhongqiang; Hu, Xinghao; Yuan, Ningyi; Ding, Jianning
Abstract : A compressible graphene aerogel converts mechanical compression energy to electrical energy in organic and aqueous electrolytes. Abstract : Mechanical energy harvesters are widely studied because of their diverse applications, such as harvesting ocean wave energy, self-powered wireless sensors, portable power supplies and so on. To be feasible, an energy harvester needs to provide a high output current and voltage, in addition to being environmentally friendly. Hence, in this study, a new energy harvester is developed via reversible deformation of a three-dimensional graphene aerogel which was immersed in a salt solution. The movement of solvated ions in the diffusion layer during the squeezing of the electrode induced the transmission of electrons out of graphene, resulting in electrical energy. The developed harvester can supply a power density of 11.7 W kg −1 and an energy density of 14.3 J kg −1, in addition to achieving a high energy conversion efficiency of approximately 43.2%. The device can also generate a high open-circuit voltage and short-circuit current when an external compression strain is applied. Moreover, it can be easily scaled up by being connected in series with multiple harvesters. Thus, the proposed energy harvester can not only be widely used for harvesting ocean wave energy, but also for adsorbing pollutants to prevent the pollution of ocean environments.